PENGEMBANGAN KARIR INDIVIDU DALAM KEWIRAUSAHAAN - Rahmi Widyanti; Basuki Basuki; Deli Anhar (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2023)
Individual career development can be predicted by observing individual entrepreneurial behavior and characteristics. This article aims to present the problem of self-management in the context of developing entrepreneurial characteristics and behavior. In the theory section, the author briefly discusses the nature and concept of entrepreneurship. Then, describe an enterprising individual with a primary focus on his characteristics and behavior. The practical part of this article presents concrete examples, showing how environmental factors, under what circumstances and how, they can influence the development of entrepreneurial attitudes. The author shows examples of how entrepreneurial personality starts at various stages of development, until it develops, starting from childhood, school, to higher education.